2020
DOI: 10.1093/cdn/nzaa053_105
|View full text |Cite
|
Sign up to set email alerts
|

Participation in a Nutrition Education and Demonstration Program in Rural Senegal Is Associated with Higher Household Dietary Diversity

Abstract: Objectives We conducted a non-randomized evaluation of a nutrition education program delivered by Soins de Santé Primaire in rural Senegal to identify the impact of participation on household dietary diversity scores (HDDS). We also sought to understand participant's perceptions of program strengths and weaknesses. Women participated in a single education session that emphasized hygiene, selecting from a variety of food groups, risk awareness of diet-related non-communicable diseases, and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In essence, seeing the process of preparing healthy meals positively impacts an individual’s self-assurance and ability to recreate comparable dishes in their kitchen. Consistent empirical evidence from rural Senegal has suggested that women who participated in nutrition education and FDs and nutrition education reported higher dietary diversity in the households than those who did not [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In essence, seeing the process of preparing healthy meals positively impacts an individual’s self-assurance and ability to recreate comparable dishes in their kitchen. Consistent empirical evidence from rural Senegal has suggested that women who participated in nutrition education and FDs and nutrition education reported higher dietary diversity in the households than those who did not [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jahns y colaboradores, en 2018, demostraron un incremento de la variabilidad dietética tras la intervención educativa, desde un promedio basal de 8,4 a 9,82, de manera estadísticamente significativa (29) . Sanders y colaboradores indicaron en su estudio el aumento de la variabilidad dietética de 7,6 a 9,0 para el grupo intervenido con estrategias educativas (30) . Amaro y colaboradores, en 2017, publicaron que tras la intervención educativa hubo un mejor conocimiento para adquirir alimentos saludables, con un incremento de la media de variabilidad dietética de 0,83, siendo estadísticamente significativo (31) .…”
Section: Discussionunclassified